Preparation method of nitrile rubber-based sensing composite material
Through the dispersion of nanocellulose on multi-wall carbon nanotubes, combined with nitrile rubber, nanocellulose and multi-wall carbon nanotubes, high-performance nitrile rubber-based sensing composite materials are prepared, which solves the improvement space for the existing nitrile rubber in terms of mechanical properties and electrical conductivity, and achieves high-strength and stable sensing electrical signals.
Patent Information
- Application Number
- CN202411779399.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-11
AI Technical Summary
There is room for improvement in the mechanical properties and conductivity of existing nitrile rubbers, and it is difficult to achieve high-strength and stable sensing electrical signals.
Through the dispersion of nanocellulose on multi-walled carbon nanotubes, combined with nitrile rubber, nanocellulose and multi-walled carbon nanotubes, and ultrasonic treatment, stirring and vacuum defoaming are used to prepare high-performance nitrile rubber-based sensing composite materials.
The uniform dispersion of multi-wall carbon nanotubes in nitrile rubber is achieved, which significantly improves the mechanical properties, conductive properties and friction-energizing properties of the composite material, and ensures high-strength and stable performance sensing electrical signals.
Smart Images

Figure CN119591952A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of composite sensing materials, and in particular relates to a method for preparing a nitrile rubber-based composite sensing material. Background Art
[0002] Nitrile rubber (NBR) is a copolymer made of acrylonitrile and butadiene monomers, known for its excellent oil resistance, wear resistance, heat resistance and air tightness. These properties make NBR play an important role in many fields, such as aerospace, automobile manufacturing, rail transportation and oil field mining. However, although NBR performs well in oil resistance and heat resistance, there is still room for improvement in mechanical properties and electrical conductivity.
[0003] Gao Zhiyi, in his paper titled "Research and Application of Flexible Sensor Devices and Their Integration in the Field of Human Sensory Systems", developed bionic sensors and their integrated systems that can simulate the functions of the human sensory system, and conducted a series of research work in terms of device structure design, material selection, and systematic integration. A self-healing electronic skin based on the integration of pressure sensors and temperature sensors was designed, which can detect and identify different stimuli and has self-recovery capabilities. Polyurethane, polyurethane@multi-walled carbon nanotubes, and cellulose nanocrystals@carboxylated nitrile rubber@polyethyleneimine with good elasticity, flexibility, and self-healing capabilities were used as pressure-sensitive materials, temperature-sensitive materials, and substrates, respectively, and an electronic skin with integrated temperature and pressure sensing functions was made by hot pressing. Each type of sensor inside the electronic skin only responds quickly and accurately to the target stimulus. At the same time, due to the self-healing ability of polyurethane and cellulose nanocrystals@nitrile rubber@polyethyleneimine, it also enables self-repair after damage, and the repaired electronic skin still maintains good temperature sensitivity and pressure sensitivity. In addition, a 5×5 device array was made based on this electronic skin device, which can simultaneously image pressure and temperature distribution and maintain self-repair capabilities. The electronic skin device inspires new ideas in the fields of artificial skin, human-machine interface and biological monitoring equipment. However, the paper did not achieve high-intensity and stable sensing electrical signals. Summary of the invention
[0004] The purpose of the present invention is to solve the above technical problems and provide a method for preparing a nitrile rubber-based sensing composite material.
[0005] The preparation method of a nitrile rubber-based sensing composite material of the present invention is carried out according to the following steps:
[0006] Step 1, subjecting the nanocellulose prepared by TEMPO oxidation method to ultrasonic treatment; then, stirring the nanocellulose after ultrasonic treatment; after repeating the ultrasonic treatment and stirring operations, a treated nanocellulose dispersion is obtained, wherein the nanocellulose accounts for 0.2-0.6% of the mass of the nitrile rubber-based sensing composite material, and is set aside;
[0007] Step 2, dripping glycerol into the nanocellulose dispersion prepared in step 1, ultrasonically treating, and stirring to obtain a nanocellulose mixed solution for standby use;
[0008] Step 3, adding multi-walled carbon nanotubes to the nanocellulose mixed solution treated in step 2, stirring until the multi-walled carbon nanotubes are completely immersed in the nanocellulose, and then performing ultrasonic treatment to obtain a mixture of multi-walled carbon nanotubes and nanocellulose, wherein the multi-walled carbon nanotubes account for 0.4-0.8% of the mass of the nitrile rubber-based sensing composite material;
[0009] Step 4, adding nitrile rubber latex to the mixture of multi-walled carbon nanotubes and nanocellulose obtained in step 3 and stirring to obtain a mixed solution;
[0010] Step 5, placing the mixed solution of step 4 in a vacuum degassing machine for vacuum degassing and setting aside;
[0011] Step 6: Place the mixed solution after vacuum degassing in a vacuum drying oven for vacuum drying, thereby completing the preparation of the nitrile rubber-based sensing composite material.
[0012] Furthermore, the preparation of nanocellulose by TEMPO oxidation method described in step 1 is to oxidize the nanocellulose with TEMPO having a mass concentration of 1%.
[0013] Furthermore, the ultrasonic treatment in step 1 is carried out under the conditions of an ultrasonic power of 200 to 400 W and an ice water bath for 5 to 20 minutes.
[0014] Furthermore, in step 2, the volume ratio of the nanocellulose dispersion to glycerol is 10-30:1; wherein the volume concentration of glycerol is 99%.
[0015] Furthermore, the ultrasonic treatment in step 2 is carried out under the conditions of an ultrasonic power of 200 to 400 W and an ice-water bath for 1 to 10 min; the stirring is magnetic stirring, and the magnetic stirring time is 10 to 30 min.
[0016] Furthermore, the mass concentration of the multi-walled carbon nanotubes is 96-98%.
[0017] Furthermore, the stirring in step 1, step 2, step 3 and step 4 is all performed by magnetic stirring, and the magnetic stirring speed is 200-400 rpm / min.
[0018] Furthermore, the mass concentration of the nitrile rubber emulsion in step 4 is 40-60%.
[0019] Furthermore, the vacuum degassing treatment conditions in step 5 are: vacuum degassing at a speed of 800-1000 rpm / min for 20 minutes, and then switching to 1000-1200 rpm / min to continue vacuum degassing.
[0020] Furthermore, the drying temperature in step 6 is 70°C.
[0021] Nanocellulose (CNF), as a lightweight and high-strength material, has unique advantages in providing excellent mechanical reinforcement and dispersion effects. First, nanocellulose has a large specific surface area and a high Young's modulus, which enables it to provide significant mechanical reinforcement in composite materials. Due to its nanoscale size and high aspect ratio, nanocellulose can form an effective interface interaction with the matrix material, thereby enhancing the mechanical properties of the composite material. Secondly, the surface of nanocellulose is rich in hydroxyl groups, which can interact with the matrix material through hydrogen bonds to enhance the cohesion and overall strength of the composite material. Furthermore, the hierarchical structure of nanocellulose enables it to form an effective mechanical support in the composite material, similar to the structure of trees in nature. This structure helps to disperse stress and improve the toughness and strength of the material. In addition, nanocellulose also has a good dispersion effect, and the surface properties and interfacial compatibility of nanocellulose are the key to its application performance. Through electrostatic repulsion and steric hindrance, nanocellulose can achieve good dispersibility in a variety of solvents and polymer matrices. It can have a good dispersion effect on multi-walled carbon nanotubes, effectively solving the disadvantage of uneven dispersion caused by the aggregation of multi-walled carbon nanotubes.
[0022] Multi-walled carbon nanotubes (MWCNTs) have extremely high electrical conductivity, which is mainly due to the sp 2 Hybridization and the hexagonal network formed. This structure allows electrons to flow freely in the tube, thus showing excellent electrical conductivity. When a small amount of multi-walled carbon nanotubes are doped, the multi-walled carbon nanotubes can be dispersed more evenly through ball milling, forming a three-dimensional conductive channel between the microstructures, which is beneficial to the transport of carriers and gradually increases the conductivity of the sample. However, ball milling can only solve the problem of a small amount of doping. When the doping amount is excessive, the problem of uneven dispersion will still occur. Nanocellulose can effectively disperse multi-walled carbon nanotubes. By adding nanocellulose, the problem of uneven dispersion of multi-walled carbon nanotubes can be effectively solved.
[0023] Through the dispersion of nanocellulose on multi-walled carbon nanotubes, nitrile rubber, nanocellulose and multi-walled carbon nanotubes can be combined to prepare a high-performance composite material with excellent mechanical properties, electrical conductivity and thermal stability. This material has a wide range of application potential in the field of flexible sensing. This composite material can be used to develop high-performance flexible sensors that can adapt to various bends and deformations while maintaining stable electrical properties. These sensors can be used in wearable devices, health monitoring systems, and human-computer interaction technologies to provide real-time health data and environmental feedback.
[0024] The present invention has the following beneficial effects:
[0025] The method of the present invention achieves uniform dispersion of multi-walled carbon nanotubes in nitrile rubber at room temperature through the dispersion effect of nanocellulose on multi-walled carbon nanotubes, and at the same time improves the mechanical properties, electrical conductivity and triboelectric properties of the nitrile rubber / nanocellulose / multi-walled carbon nanotube composite film. The elasticity of nitrile rubber, the high strength of nanocellulose, and the electrical conductivity and thermal stability of multi-walled carbon nanotubes are combined together to achieve multiple optimizations of performance.
[0026] The addition of multi-walled carbon nanotubes as fillers further enriches the performance of the material. Its unique electrical conductivity makes the composite material have great application potential in the electronic and electrical fields. For example, in flexible electronic devices, the electrical conductivity and flexibility of the material enable it to adapt to complex structural designs and dynamic deformations, and maintain good electrical properties. In addition, the thermal conductivity of carbon nanotubes effectively improves the thermal stability of the material, so that it can still maintain stable performance in a high temperature environment and is not prone to thermal degradation. However, multi-walled carbon nanotubes are prone to flocculation in composite materials. The present invention effectively overcomes the common flocculation phenomenon by first dispersing them in nanocellulose, which not only improves the uniformity of the material, but also optimizes its electrical conductivity and mechanical properties.
[0027] The nitrile rubber / nanocellulose / multi-walled carbon nanotube composite material significantly improves the overall performance of the composite material by comprehensively utilizing the advantages of the three materials, and achieves high-strength, stable performance sensing electrical signals. This material not only achieves stable enhancement of sensing electrical performance, but also shows wide application potential in the field of flexible electronic devices due to its unique structure and performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The figures are the actual effect pictures without adding nanofibers and after adding nanocellulose; among them, figure a is the actual effect picture without adding nanofibers; figure b is the actual effect picture after adding nanocellulose;
[0029] Figure 2These are performance investigation diagrams of nanocellulose concentration and multi-walled carbon nanotube concentration; among them, Figure a is the stress-strain curve diagram of different nanocellulose concentrations; Figure b is the resistance curve diagram of different multi-walled carbon nanotube concentrations; and Figure c is the voltage signal curve diagram of different multi-walled carbon nanotube concentrations. DETAILED DESCRIPTION
[0030] In order to make the objectives, technical solutions and advantages of the embodiments of the present invention more clearly understood, the spirit of the contents disclosed by the present invention will be described in detail below. After understanding the embodiments of the contents of the present invention, any technician in the relevant technical field can change and modify them according to the techniques taught by the contents of the present invention without departing from the spirit and scope of the contents of the present invention.
[0031] The exemplary embodiments of the present invention and the description thereof are used to explain the present invention but are not intended to limit the present invention.
[0032] Example 1
[0033] The preparation method of a nitrile rubber-based sensing composite material of this embodiment is as follows:
[0034] 1) The nanocellulose oxidized by TEMPO with a mass concentration of 1% was subjected to an ice-water bath ultrasound treatment at a power of 300 W for 10 minutes, and the treated nanocellulose was magnetically stirred at 300 rpm / min to achieve a uniform dispersion effect.
[0035] 2) Take 40 ml of nanocellulose dispersion, add 2 ml of 99% glycerol dropwise into the nanocellulose dispersion, then perform ultrasonic treatment at 300W for 5 minutes in an ice water bath, stir with a magnetic stirrer for 20 minutes, and set aside.
[0036] 3) 0.2 g of multi-walled carbon nanotubes with a mass concentration of 97% was added to the nanocellulose after ultrasonic treatment, and stirred at 300 rpm / min until the multi-walled carbon nanotubes were completely immersed in the nanocellulose, and then ultrasonic treatment was performed at 300 W for 20 minutes.
[0037] 4) After adding 5 ml of 50% mass concentration nitrile rubber latex, the mixture was placed in a magnetic stirrer and stirred at 300 rpm / min;
[0038] 5) Place the mixed solution in a vacuum degassing machine, set the vacuum degassing speed to 900 rpm / min for 20 minutes, then switch to 1200 rpm / min to continue vacuum degassing.
[0039] 6) The mixed solution after vacuum degassing is placed in a vacuum drying oven at 70°C for vacuum drying.
[0040] Comparative Example 1
[0041] This comparative example is different from Example 1 in that no nanocellulose is added. Other aspects are the same as Example 1.
[0042] like Figure 1 As shown, Example 1 effectively overcomes the common flocculation phenomenon of multi-walled carbon nanotubes in composite materials through the excellent dispersibility of nanocellulose. This dispersion effect not only improves the uniformity of the material, but also optimizes its conductivity and mechanical properties. The addition of nanocellulose makes the multi-walled carbon nanotubes more evenly distributed in the matrix, thereby significantly improving the overall performance of the composite material and ensuring that it exhibits excellent stability and reliability in application.
[0043] The stress-strain curves at different nanocellulose concentrations are shown in Figure 2. Figure 2 As shown in (a), it can be seen that the mechanical properties of the material are the strongest when the nanocellulose concentration is 0.4%. This is mainly because at this concentration, the best interaction is formed between nanocellulose and the matrix, thereby improving the overall strength and toughness of the composite material. The uniform dispersion and effective interface bonding of nanocellulose enable stress to be transmitted more effectively in the composite material, reducing stress concentration and crack formation. In addition, the 0.4% nanocellulose concentration may promote the formation of hydrogen bonds and enhance the interaction between molecules, thereby improving the mechanical properties of the material. This optimized nanocellulose concentration not only enhances the material's load-bearing capacity, but also may improve its fatigue resistance and durability, which are critical for many engineering applications. Therefore, a nanocellulose concentration of 0.4% is considered to be an ideal addition level that balances the reinforcement effect and processing performance, providing a valuable reference for the design and application of composite materials.
[0044] Figure 2 (b) shows the resistance of the material at different multi-walled carbon nanotube concentrations. Multi-walled carbon nanotubes have the ability to conduct electricity. With the addition of multi-walled carbon nanotubes, the conductivity is enhanced and the resistance is reduced. This is mainly because the addition of multi-walled carbon nanotubes forms a more efficient electron transmission path, which improves the conductivity of the material. The interaction between multi-walled carbon nanotubes and the interaction with the matrix enhances the mobility of electrons, thereby reducing resistance. By rationally designing and optimizing the concentration and processing of multi-walled carbon nanotubes, the electrical properties of the composite material can be significantly improved.
[0045] Figure 2(c) shows the voltage signal when the nitrile rubber / multi-walled carbon nanotube / nanocellulose composite material, as an electrostatic induction material, is in contact and separation with PTFE. As shown in the figure, the addition of multi-walled carbon nanotubes is beneficial to improving the electrical properties, and the performance is the highest when the concentration of multi-walled carbon nanotubes is about 0.6%. This is because multi-walled carbon nanotubes have excellent electrical conductivity. When added to the composite material, they can form a more continuous conductive network, thereby improving the electrical conductivity of the material. With the increase of the content of multi-walled carbon nanotubes, the electron transmission path inside the composite material is optimized, the electron mobility is improved, resulting in reduced resistance and enhanced electrical properties. In particular, at a concentration of 0.6%, the multi-walled carbon nanotubes may form the best interface bonding and charge transfer channels with the nitrile rubber and nanocellulose, so that the electrostatic induction performance of the composite material reaches the best state. This optimized electrostatic induction performance is of great significance for improving the application potential of composite materials in sensors, energy collection and other electronic devices.
Claims
1. A method for preparing a nitrile rubber-based sensing composite material, characterized in that It is carried out according to the following steps: Step 1, subjecting the nanocellulose prepared by TEMPO oxidation method to ultrasonic treatment; then, stirring the nanocellulose after ultrasonic treatment; after repeating the ultrasonic treatment and stirring operations, a treated nanocellulose dispersion is obtained, wherein the nanocellulose accounts for 0.2-0.6% of the mass of the nitrile rubber-based sensing composite material, and is set aside; Step 2, dripping glycerol into the nanocellulose dispersion prepared in step 1, ultrasonically treating, and stirring to obtain a nanocellulose mixed solution for standby use; Step 3, adding multi-walled carbon nanotubes to the nanocellulose mixed solution treated in step 2, stirring until the multi-walled carbon nanotubes are completely immersed in the nanocellulose, and then performing ultrasonic treatment to obtain a mixture of multi-walled carbon nanotubes and nanocellulose, wherein the multi-walled carbon nanotubes account for 0.4-0.8% of the mass of the nitrile rubber-based sensing composite material; Step 4, adding nitrile rubber latex to the mixture of multi-walled carbon nanotubes and nanocellulose obtained in step 3 and stirring to obtain a mixed solution; Step 5, placing the mixed solution of step 4 in a vacuum degassing machine for vacuum degassing and setting aside; Step 6: Place the mixed solution after vacuum degassing in a vacuum drying oven for vacuum drying, thereby completing the preparation of the nitrile rubber-based sensing composite material.
2. The method for preparing the nitrile rubber-based sensing composite material according to claim 1, characterized in that The preparation of nanocellulose by TEMPO oxidation method described in step 1 is to oxidize the nanocellulose with TEMPO having a mass concentration of 1%.
3. The method for preparing the nitrile rubber-based sensing composite material according to claim 1, characterized in that The ultrasonic treatment described in step 1 is carried out at an ultrasonic power of 200 to 400 W in an ice water bath for 5 to 20 minutes.
4. The method for preparing the nitrile rubber-based sensing composite material according to claim 1, characterized in that In step 2, the volume ratio of the nanocellulose dispersion to glycerol is 10-30:1; wherein the volume concentration of glycerol is 99%.
5. The method for preparing the nitrile rubber-based sensing composite material according to claim 1, characterized in that The ultrasonic treatment described in step 2 is carried out under the conditions of ultrasonic power of 200-400W and ice water bath for 1-10 minutes; the stirring is magnetic stirring, and the magnetic stirring time is 10-30 minutes.
6. The method for preparing the nitrile rubber-based sensing composite material according to claim 1, characterized in that The mass concentration of the multi-walled carbon nanotubes is 96-98%.
7. The method for preparing the nitrile rubber-based sensing composite material according to claim 1, characterized in that The stirring in step 1, step 2, step 3 and step 4 is all performed by magnetic stirring, and the magnetic stirring speed is 200-400 rpm / min.
8. The method for preparing the nitrile rubber-based sensing composite material according to claim 1, characterized in that The mass concentration of the nitrile rubber latex in step 4 is 40-60%.
9. The method for preparing the nitrile rubber-based sensing composite material according to claim 1, characterized in that The vacuum degassing treatment conditions in step 5 are: vacuum degassing at a speed of 800-1000 rpm / min for 20 minutes, and then switching to 1000-1200 rpm / min to continue vacuum degassing.
10. The method for preparing a nitrile rubber-based sensing composite material according to claim 1, characterized in that The drying temperature in step 6 is 70°C.